Efektivitas Konsumsi Jus Bayam Merah Dan Jus Tomat Terhadap Peningkatan Kadar Hemoglobin Pada Ibu Hamil Trimester III Di Klinik Kita Grogol Depok Tahun 2023 - Retno Ekawati; Indri Sarwili; Nina Nina (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Anemia in pregnancy is a condition where the hemoglobin level of a pregnant woman is below 11 g/dl. The high rate of anemia in third trimester pregnant women at Kita Clinic Depok is a health problem that needs attention. One non-pharmacological effort to increase hemoglobin levels is to consume red spinach juice and tomato juice. This research uses a Quasy Experiment design, with a Two Group Pretest Posttest Design. The samples in this study were pregnant women in the third trimester who experienced mild anemia, of which 15 pregnant women were given red spinach juice and 15 pregnant women were given tomato juice for 7 days. The sampling technique used was Purposive Sampling. Based on the research results, it shows that from pretest data the average hemoglobin level of pregnant women before being given red spinach juice was 10.1 gr/dl, whereas before being given tomato juice the average hemoglobin level of pregnant women was 10.2 gr/dl. In the posttest data, it was found that the average hemoglobin level of pregnant women after being given red spinach juice was 11.1 gr/dl, whereas after being given tomato juice the average hemoglobin level of pregnant women was 11.2 gr/dl. The results of the paired sample T-Test show that the value (p-value 0.000 < 0.05) states that the Ha hypothesis is accepted and Ho is rejected. There is effectiveness between the consumption of red spinach juice and tomato juice in increasing hemoglobin levels in pregnant women in the third trimester at Kita Grogol Depok Clinic in 2023. Collaboration is needed with specialist obstetricians and gynecology (Obgyn) and midwives providing nutrition education for pregnant women or counseling with provide information about the importance of foods containing iron and carry out routine checks to monitor hemoglobin levels to prevent pregnancy anemia.